External Beam Accelerated Partial Breast Irradiation: Dosimetric Assessment of Conformal and Three Different Intensity Modulated Techniques - Stelczer, Gábor (Radiol Oncol, 2019)
BACKGROUND: The aim of the study was to evaluate and compare four different external beam radiotherapy techniques of accelerated partial breast irradiation (APBI) considering target coverage, dose to organs at risk and overall plan quality. The investigated techniques were three dimensional conformal radiotherapy (3D-CRT), “step and shoot” (SS) and “sliding window” (SW) intensity-modulated radiotherapy (IMRT), intensity-modulated arc therapy (RA). PATIENTS AND METHODS: CT scans of 40 APBI patients were selected for the study. The planning objectives were set up according to the international recommendations. Homogeneity, conformity and plan quality indices were calculated from volumetric and dosimetric parameters of target volumes and organs at risk. The total monitor units and feasibility were also investigated. RESULTS: There were no significant differences in the coverage of the target volume between the techniques. The homogeneity indices of 3D-CRT, SS, SW and RA plans were 0.068, 0.074, 0.058 and 0.081, respectively. The conformation numbers were 0.60, 0.80, 0.82 and 0.89, respectively. The V(50%) values of the ipsilateral breast for 3D-CRT, SS, SW and RA were 47.5%, 40.2%, 39.9% and 31.6%, respectively. The average V(10%) and V(40%) values of ipsilateral lung were 13.1%, 28.1%, 28%, 36% and 2.6%, 1.9%, 1.9%, 3%, respectively. The 3D-CRT technique provided the best heart protection, especially in the low dose region. All contralateral organs received low doses. The SW technique achieved the best plan quality index (PQI). CONCLUSIONS: Good target volume coverage and tolerable dose to the organs at risk are achievable with all four techniques. Taking into account all aspects, we recommend the SW IMRT technique for APBI.